Hepatic Deficiency of Augmenter of Liver Regeneration Predisposes to Nonalcoholic Steatohepatitis and Fibrosis. Issue 5 (22nd October 2020) - Kumar, Sudhir; Verma, Alok K.; Rani, Richa; Sharma, Akanksha; Wang, Jiang; Shah, Shimul A.; Behari, Jaideep; Salazar Gonzalez, Rosa; Kohli, Rohit; Gandhi, Chandrashekhar R.
Abstract : Background and Aims: The augmenter of liver regeneration (ALR) protein is critical for lipid homeostasis and mitochondrial function. We investigated high‐fat/high‐carbohydrate (HF/HC) diet–induced nonalcoholic fatty liver disease (NAFLD) in wild‐type (WT), hepatocyte‐specific ALR‐knockout (ALR‐H‐KO), and ALR‐heterozygous (ALR‐H‐HET) mice. ALR was measured in serum of human nonalcoholic steatohepatitis (NASH) and NASH‐induced cirrhosis (serum and liver). Approach and Results: HF/HC feeding decreased ALR expression in all groups of mice. The otherwise normal ALR‐H‐HET mice gained more weight and steatosis than WT mice when challenged metabolically with the HF/HC diet; ALR‐H‐KO mice gained the least weight and had the least steatosis. These findings were consistent with correspondingly increased triglycerides and cholesterol and altered expression of carnitine palmitoyltransferase 1a, sterol regulatory element‐binding protein, acetyl coenzyme A carboxylase, and fatty acid synthase. All HF/HC‐fed mice developed insulin resistance, the magnitude being lower in ALR‐H‐KO mice. HF/HC‐fed ALR‐H‐HET mice were more resistant to glucose challenge than WT or ALR‐H‐KO mice. The frequency of tumor necrosis factor alpha–producing, interleukin 6 (IL6)–producing, and IL17‐producing cells was greater in ALR‐H‐KO than ALR‐H‐HET and lowest in WT mice. HF/HC feeding did not increase their number in ALR‐H‐KO mice, and the increase in ALR‐H‐HET was greater than that in WT mice except for IL17 cells. Cluster of differentiation 25–positive (CD25 + ) forkhead box P3–positive CD4 + regulatory T‐cell frequency was lower in ALR‐H‐HET than WT mice and further reduced in ALR‐H‐KO mice; HF/HC reduced regulatory T‐cell frequency only in WT mice. HF/HC‐fed ALR‐H‐HET, but not WT, mice developed fibrosis; and ALR‐H‐KO mice progressed to cirrhosis. White adipose tissue of HF/HC‐fed ALR‐deficient mice developed strong inflammation, indicating bidirectional interactions with the liver. Hepatic and serum ALR levels were significantly reduced in patients with NASH‐cirrhosis. Serum ALR was also significantly lower in patients with NASH. Conclusions: Hepatic ALR deficiency may be a critical predisposing factor for aggressive NAFLD progression.